Motivações para adoção dos fatores ambientais, sociais e de governança (ASG) às análises de investimento pelos gestores de ativos - Naum, Cristine Marian (2018)
Since the mid-twentieth century, climate change has had a significant impact in several economy sectors whilst scandals related to corporate governance as well as political and social instability have directly influenced the value of companies and also altered the way investments are considered. Due to this scenario, environmental, social and corporate governance factors have been taken into account in business analysis, demanding engagement, transparency and new forms for data evaluation. In search for identifying the motivations for the integration of environmental, social and governance factors (ESG) into investment analysis, as well as evaluating the use of this data, the present research discusses the challenges imposed by this model of asset analysis through the dialogue with nine actors and institutions related to the financial market. As to create a qualitative and exploratory methodological approach, interviews were held in depth using a semi structured script with five new Brazilian Asset Management professionals and with institutions related to this topic. For the development of this study, a theoretical revision of the evolution of sustainability of the financial market was necessary, which imposes new challenges to the investment management. According to the results of this research, the main motivators for the adoption of ESG factors to investment analyses are the adoption of the Principles for Responsible Investment (PRI) by the greatest financial institutions in Brazil, followed by the awareness of the rise of financial and reputational risks originated from company operations. The data sources used in this research are diverse, with special emphasis on sustainability reports released by companies. However, a lack of comparability, reliability, history, format and integration in the companies’ results still damages the use of this information by other entities. The present study contributes with the adoption of ESG factors by several segments of the financial sector, as well as with the improvement of management of those which already integrate them. Besides, companies will be able to better comprehend the importance of adequate communication and of the quality of data for investors through sustainability reports.